Pragmatique topique, énonciation et linguistique de corpus: essai de caractérisation du corpus cartésien - Sarfati, Georges-Elias (Travaux neuchâtelois de linguistique, 2012)
This article deals with the question of enunciation and corpus linguistics in the perspective of the linguistic theory of common sense (Topics pragmatics). According to the later, a discourse have to be understood in connection with a specific social practice. In that view, each kind of discourse has its own dynamics that includes a "canon", a "vulgate" and a "doxa". This conception of discourse renews the concept of "corpus", since it shows that corpus linguistics have to take into account those three levels of dynamic structuration. This paper is an attempt to demonstrates the relevance of this pragmatics conception: it takes as an example the caracterization of the "cartesian corpus".